Ikan Introduksi Oxyeleotris marmorata, Bleeker (1852): Populasi, Laju Exploitasi dan Pengendaliannya di Waduk Sempor, Kebumen - Windiariani Lestari; Siti Rukhayah; Tutilah Jamilatun (Fakultas Biologi | Universitas Jenderal Soedirman, 2019)
Oxyeleotris marmorata Bleeker or marble goby originally from China and is introduced to Indonesia in 1927. This predator fish could be a threat to freshwater fish diversity, thus its population should be controlled. In order to support their control efforts, this research attempted to evaluate the population size and exploitation rate of O.marmorata in Sempor Reservoir, Kebumen. Survey with purposive random sampling were applied by dividing the Sempor Reservoir into three parts (inlet, middle and outlet) and each part was represented by two sites. The population sizes of fish were analyzed using F-test and the exploitation rates of O.marmorata were analyzed using FiSAT II. The result shown that the population sizes of O.marmorata in inlet, middle and outlet were is different. (Fcal= 7.544 with P= 0.03). The fish population in middle possessed L∞ = 39.06, K = 2.0 and t0 = -0.44, and fish population in outlet with properties L∞ = 37.59, K = 2.1, and t0 = -0.42. The growth patterns of O.marmorata in both parts were relatively similar. The mortality of O.marmorata in the middle part was more caused by fishing activities, meanwhile in the outlet, the mortality occurred naturally. The exploitation rate in middle (E= 0.55) and in outlet parts (E=0.10). It seems that the middle part of Sempor Reservoir was 5 times more exploited than in the outlet part. Population control could be conducted by fishing O marmorata with 13.38-17.30 cm in length in outlet part and fishing (E) should not more than 0.5.